Protocol Stack-Aware Comparison of Centroid Localization Algorithms Based on Anchor Density Using Cooja - Turan, I.H.; Yıldız, D.; Demirci, S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Location reconnaissance of sensor nodes is crucial for many outdoor applications. In fact, some outdoor wireless sensor networks are deployed solely for location information. However, adding a GPS module to each node can increase the cost of the wireless sensor network. Therefore, software-based location estimation using radio signals becomes necessary. Hardware without a GPS module requires nodes with known locations in the network. To keep the cost of the network economically reasonable, the density of anchor nodes in the network with expensive nodes that have GPS modules should be investigated. In this study, an alternative method has been developed for transmitting localization packets in Contiki-NG firmware Wireless Sensor Networks (WSNs), as point-to-point communication is not suitable for the nature of WSNs. Using the method, the minimum anchor node density and transmission range required for localization in mesh topologies, was investigated according to negligible location estimation errors with Cooja network simulation environment. Three centroid-based algorithms have been compared based on localization error and localization ratio. At the end of the study, the minimum transmission range and anchor density ratio required for localization algorithms were determined. It was shown how effective the MAC policy was up to which transmission range. It was demonstrated how incorrect conclusions could be reached when network protocol stack requirements were not considered. © 2023 IEEE.
Aselsan; CIS ARGE; Yeditepe University
Keywords: Contiki-NG; Cooja; Localization; Path-Loss Aware Estimation; Range-Free Techniques; WSN